PENGARUH MODEL EXAMPLE NON EXAMPLE TERHADAP HASIL BELAJAR IPS KELAS V SEKOLAH DASAR - Wijaya, Hendra; Asran, Mastar; ., Sukmawati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The Influence of Example Non Example models on learning outcomes Sosial Science V Grade Elementary School. This study aimed to gain information about the influence of the model Example NonExample of the learning outcomes of Social Sciences Grade V Elementary School. The method in this research is a form of quasi-experimental method. Data collection technique is the direct observation and measurement techniques. The data collection tool is aobservation sheet and test fields totaling 20 questions. The results of the average pre-test is 60.27 with a standard deviation is 15.28. The results of the average post-test was 80.22 with a standard deviation is 11.59. The results of normality test, both normally distributed. T test results obtained t_hitung 8.43 with df = 31-1 = 30 and a significance level (?) = 5% price obtained price ttabel = 2.042, was tcount ? ttable. It can be concluded that Ho is rejected and Ha is accepted. This means that there is an influence in model of Example Non Example of the learning outcomes of Social Sciences Grade V Elementary School 12 South Pontianak. Keywords: Example Non Example, Learning Outcomes Abstrak: Pengaruh model Example Non Example terhadap hasil belajar IPS Kelas V SD. Penelitian ini bertujuan untuk mendapatkan informasi tentang pengaruh model Example Non Example terhadap hasil belajar Ilmu Pengetahuan Sosial siswa kelas V Sekolah Dasar. Metodedalam penelitian ini adalah metode eksperimen dengan bentukquasi exsperimental design.Teknik pengumpul data yang digunakan adalah teknik observasi langsung dan teknik pengukuran.Alat pengumpul data yang adalah lembar observasi dan tes soal isian yang berjumlah 20 soal.Hasil rata-rata pre-test adalah 60,27 dengan standar deviasi 15,28. Hasil rata-rata post-test adalah 80,22dengan standar deviasi 11,59. Hasil uji normalitas, keduanya berdistribusi normal. Hasiluji t diperoleh 8,43 dengan df = 31 1 = 30 dan taraf signifikan (?) = 5% diperoleh harga = 2,042, ternyata ? . Dapat disimpulkan bahwa Ho ditolak dan Ha diterima. Artinya terdapat pengaruh model Example Non Example terhadap hasil belajar Ilmu Pengetahuan Sosial siswa kelas V Sekolah Dasar Negeri 12 Pontianak Selatan. Kata Kunci: Example Non Example, Hasil Belajar